A new general iterative method for a finite family of nonexpansive mappings in hilbert spaces - Suthep Suantai (2018)
We introduce a new general iterative method by using the K -mapping for finding a common fixed point of a finite family of nonexpansive mappings in the framework of Hilbert spaces. A strong convergence theorem of the purposed iterative method is established under some certain control conditions. Our results improve and extend the results announced by many others. Copyright 2010 Urailuk Singthong and Suthep Suantai.